Creep of columnar-grained ice at low stress - Gold, L. W. (1983)
An investigation was undertaken of the creep of columnar- grained ice under constant compressive stresses of 98 and 59 kPa in order to extend the observed relationship between strain-rate and stress further into the low-stress region. Stress was applied perpendicular to the long direction of the grains. Observations were made for temperatures between -5 and -40 degrees C. The steady-state creep rate for secondary creep was not yet attained for strain of 1.4% and stress of 98 kPa. An initial yield was observed at that stress in the strain range of 0.2 to 0.3%, similar to that seen at higher stress. The observations showed that the strain-rate tended to a linear dependence on stress below 49 kPa and that more than one dislocation process with different values for the stress exponent may contribute to the strain at higher stresses. An activation energy of 63 kJ mol[-1] was consistent with the observed temperature dependence of the strain-rate. Straining ice to a given strain under a stress of about 0.3 MPa and then reducing the load may be a convenient way to study the stress, strain and temperature dependence of the strain-rate at low stress. On a entrepris une étude du fluage de la glace columnaire sous contraintes de compression constantes de 98 et 49 kPa afin d'étendre la relation observée entre le taux de déformation et la charge dans la région des faibles contraintes. Une contrainte a été appliquée perpendiculairement au plus long axe des grains. On a effectué des observations pour des températures variant entre -5 degrés C et -40 degrés C. Le taux de fluage en régime permanent pour le fluage secondaire n'avait pas encore été atteint pour une déformation de 1,4% et une contrainte de 98 kPa. Pour cette contrainte, dans la gamme des déformations de 0,2 à 0,3% on a observé un écoulement initial comparable à celui observé pour des contraintes plus élevées. Les observations indiquent que le taux de déformation avait tendance à dépendre linéairement de la contrainte pour moins de 49 kPa et que plus d'un processus ...